The Investigation of Designers’ Reflective Practice Activity Using Verbal Protocol Analysis - Kamil, Muhammad Jameel Mohamed; Abidin, Shahriman Zainal; Hassan, Oskar Hasdinor (2018)
This paper intends to investigate the cognitive process of designers’ sketching activity based on their understanding towards the value of unconscious interaction and cognitive of human behavior in the everyday products. Using Verbal Protocol Analysis (VPA) as the main approach, four Malaysian designers from different levels of expertise worked on product design tasks in relation to four attributes of unconscious interaction in everyday human behavior. The VPA data were coded and analyzed based on Schon’s theoretical framework of reflective practice. At the end of the study, the descriptive analysis of each designers’ design activity was presented based on Andreasen’s level of abstraction. The result of the study illustrates remarkable strategies differences in the patterns of designer’s reflective practice during the conceptual design process. The implications of this study clarify the significance of these approaches in gaining insights into designers' reflective practice activity.